(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This article highlights the duty of the public employee to oppose any governmental policy that goes against constitutional principles and objectives. The defense of this position is made from an organizational analysis of the State. Theoretical contributions such as the understanding of State and Domination in M. Weber, Organization in D. Katz and R.L. Khan, and Control Agency in B.F. Skinner have been used. The analysis of contingencies that control the behavior of the public employee and the understanding of the notions of State and Organizations enable greater clarity about what constitutes the role of workers in the public sector. It also highlights the importance of existing mechanisms to reduce the imbalance in power relations between governors, servants and the population.